1977
DOI: 10.2343/geochemj.11.111
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the core and implications for origin of the earth.

Abstract: AustraliaThe density of the core is about 8 percent smaller than that of pure iron under similar P, T conditions, implying the presence of a substantial amount of light element(s).Sulphur is popularly considered to be the principal light element in the core. If so, the earth accreted about 44 percent of the primordial complement of this element. To accrete sulphur as efficiently as this, and at the same time, to account for the observed depletions by much larger factors of Na, K, Mn, Rb, F, Cs, Zn and Cl, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(135 citation statements)
references
References 74 publications
8
125
1
1
Order By: Relevance
“…The solubility of oxygen in liquid Fe metal is relatively low at room pressure. At the 1 bar Fe-FeO eutectic, Fe metal contains only 0.16 wt% oxygen (Ringwood 1977). However, experiments have shown that solubility increases with both pressure and temperature (Kato & Ringwood 1989;Takahashi et al 2004).…”
Section: Oxygen Partitioning and Its Effect On The Feo/mgo Ratio Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of oxygen in liquid Fe metal is relatively low at room pressure. At the 1 bar Fe-FeO eutectic, Fe metal contains only 0.16 wt% oxygen (Ringwood 1977). However, experiments have shown that solubility increases with both pressure and temperature (Kato & Ringwood 1989;Takahashi et al 2004).…”
Section: Oxygen Partitioning and Its Effect On The Feo/mgo Ratio Of Tmentioning
confidence: 99%
“…The partitioning of oxygen during core-mantle equilibration could have also influenced the redox state of the mantle in addition to potentially contributing at least part of the light element budget of the core (Ringwood 1977;Rubie et al 2004). The solubility of oxygen in liquid Fe metal is relatively low at room pressure.…”
Section: Oxygen Partitioning and Its Effect On The Feo/mgo Ratio Of Tmentioning
confidence: 99%
“…The core is composed mainly of Fe, and comprises an outer liquid part and an inner solid part [24]. The density of the outer core is ∼ 6 % too low to be pure Fe [24,25,26,27,28], and cosmochemical and geochemical arguments show that the main light impurities are probably S, O and Si [26]. The inner core has grown over geological time by crystallisation from the outer core, and the partitioning of impurities between liquid and solid is crucial for understanding the evolution and contemporary dynamics of the core.…”
Section: Introductionmentioning
confidence: 99%
“…Further, angular momentum transfer by electromagnetic coupling from the core to the mantle also depends on electrical conductivity of the mantle. The upper mantle of the Earth is predominantly olivine and pyroxene, and it is reasonable to assume that this is the composition of the lower mantle [Ringwood, 1979]; however, at depths of about 670 km, both pyroxene and olivine undergo phase transformations to perovskite, with the additional phase magnesiowfistite being formed due to the stoichiometry of olivine [Liu, 1975].The laser-heated diamond anvil cell (LHDAC) is widely used to prepare phase assemblages of materials at pressures of Earth's mantle and core. Typically, ground-up samples are sealed from interaction with the external atmosphere by the diamonds and the gasketing material.…”
mentioning
confidence: 99%